Novel TIPP (H-Tyr-Tic-Phe-Phe-OH) analogues displaying a wide range of efficacies at the δ opioid receptor. Discovery of two highly potent and selective δ opioid agonists - Berezowska, Irena (2012)
Analogues of the δ opioid antagonist peptide TIPP (H-Tyr-Tic-Phe-Phe-OH; Tic = 1,2,3,4-tetrahydroisoquinoline3-carboxylic acid) containing various 4′-[N-(alkyl or aralkyl)carboxamido]phenylalanine analogues in place of Tyr(1) were synthesized. The compounds showed subnanomolar or low nanomolar δ opioid receptor binding affinity and various efficacy at the δ receptor (antagonism, partial agonism, full agonism) in the [(35)S]GTPγS binding assay. Two analogues, [1-Ncp(1)]TIPP (1-Ncp = 4′-[N-(2-(naphthalene-1-yl)ethyl)carboxamido] phenylalanine) and [2-Ncp(1)]TIPP (2-Ncp = 4′-[N-(2-(naphthalene-2-yl)ethyl)carboxamido]phenylalanine), were identified as potent and selective δ opioid agonists.